Investigation Of Stacking Layer Effect On The Kenaf Hybrid Composite Mechanical Properties For Automotive Application - Mohd Khaiyazi, Khairunnisa (Progress in Aerospace and Aviation Technology, 2023)
The field of automotive manufacturing continually seeks innovative, sustainable materials with an emphasis on mechanical robustness. The study is aimed at investigating the Kenaf fibres’ potential as an alternative to synthetic fibre composites in automotive bumper beams, shedding light on the mechanical properties of this hybrid composite. The primary focus lies on the impact of different fibre orientations: unidirectional, bidirectional, and 45-degree angles. Using the hand layup process, a natural fibre composite served as the material for constructing the sample, tested for mechanical properties with a Universal Testing Machine. Findings from both tensile and flexural tests illuminate the mechanical properties of Kenaf fibre composite, providing valuable insights into its utilisation potential. The Kenaf hybrid composite showcased viable mechanical properties, suggesting its potential for automotive applications. The research establishes Kenaf fibres as a promising, sustainable alternative that could revolutionize the automotive industry without compromising structural integrity.